1995
DOI: 10.1182/blood.v86.3.1035.bloodjournal8631035
|View full text |Cite
|
Sign up to set email alerts
|

Role of the glycoprotein Ib-binding A1 repeat and the RGD sequence in platelet adhesion to human recombinant von Willebrand factor

et al.

Abstract: To assess the relative importance of the glycoprotein (GP) Ib binding domain and the RGDS binding site in platelet adhesion to isolated von Willebrand factor (vWF) and to collagen preincubated with vWF, we deleted the A1 domain yielding delta A1-vWF and introduced an aspartate- to-glycine substitution in the RGDS sequence by site-directed mutagenesis (RGGS-vWF). Recombinant delta A1-vWF and RGGS-vWF, purified from transfected baby hamster kidney cells, were compared with recombinant wild-type vWF (WT-vWF) in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Another primary biomarker for the hemocompatibility of RBPs is the proteolytic enzyme ADAMTS13, a metalloprotease secreted by the liver (42). As vWf unfolds from its globular form during exposure to supra-physiological shear stress, a binding site for ADAMTS13 is exposed allowing for the cleavage of vWf, thus decreasing its hemostatic potential (9,10). The present study found ADAMTS13 concentration significantly decreased with time ( Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Another primary biomarker for the hemocompatibility of RBPs is the proteolytic enzyme ADAMTS13, a metalloprotease secreted by the liver (42). As vWf unfolds from its globular form during exposure to supra-physiological shear stress, a binding site for ADAMTS13 is exposed allowing for the cleavage of vWf, thus decreasing its hemostatic potential (9,10). The present study found ADAMTS13 concentration significantly decreased with time ( Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, platelet aggregate adhesion may be promoted by the plasma glycoprotein, von Willebrand factor (vWf). Under high shear conditions, vWf unfolds (9) and binding sites that mediate adhesion and aggregation of platelets are exposed (10,11). Increased platelet aggregation and elevated vWf concentration are thus important hemocompatibility biomarkers used during the development of RBPs (4,12,13) that indicate thrombosis.…”
mentioning
confidence: 99%
“…Results showed that this mAb was able to completely block CHO‐αIIbβ3 cell adhesion and spreading on VWF (Fig 2). This was confirmed by showing that DTT‐treated CHO‐αIIbβ3 cells were unable to adhere and spread on rVWF‐RGGS (data not shown), reported as unable to bind to thrombin‐stimulated platelets (Lankhof et al , 1995).…”
Section: Inhibition Of Dtt‐stimulated Cho‐αiibβ3 Cell Adhesion and Spmentioning
confidence: 68%
“…Fourteen potential N-linked glycosylation sites are present in the canine sequence, all of which correspond to similar sites contained within the human sequence. The 2 integrin-binding sites identified in the human vWF protein sequence 29 also are conserved in the canine sequence ( Fig 1). The 3Ј untranslated region has diverged to a greater extent than the coding region (data not shown), a divergence comparable to that found between the human and bovine sequences derived for the 5Ј flanking region.…”
Section: Comparison Of the Canine And Human Sequencesmentioning
confidence: 85%